Rapid Printing of Pseudo-3D Printed SnSe Thermoelectric Generators Utilizing an Inorganic Binder - Geraint Howells (ACS Applied Materials & Interfaces, 2023)
There has been much interest in tin selenide (SnSe) in the thermoelectric community since the discovery of the record zT in the material in 2014. Manufacturing techniques used to produce SnSe are largely energy-intensive (e.g., spark plasma sintering); however, recently, in previous work, SnSe has been shown to be produced via a low embodied energy printing technique, resulting in 3D samples with high zT values (up to 1.7). Due to the additive manufacturing technique, the manufacturing time required was substantial. In this work, 3D samples were printed using the inorganic binder sodium metasilicate and reusable molds. This facilitated a single-step printing process that substantially reduced the manufacturing time. The printed samples were thermally stable through multiple thermal cycles, and a peak zT of 0.751 at 823 K was observed with the optimum binder concentration. A proof-of-concept thermoelectric generator produced the highest power output of any reported printed Se-based TEG to date.